The Phyllomedusa perinesos group (Anura: Hylidae) is derived from a Miocene Amazonian Lineage - Ron, Santiago R.; Almendariz, Ana; Cannatella, David C. (Zootaxa, 2013)
The Phyllomedusa perinesos group is composed of four species that inhabit cloud forests in the eastern Andean slopes. We estimated the phylogenetic relationships among them and their closest relatives using mitochondrial DNA sequences. Our results confirm the monophyly of the group and a close relationship with the Amazonian species Phyllomedusa atelopoides and Phyllomedusa tomopterna. A chronogram indicates that the group originated during the Miocene and the contemporary species diverged from their closest relatives during the Miocene and early Pliocene. The timing of the group’s origin suggests that its evolution was linked to the rise of the eastern Andes. Based on the phylogeny we expand the species content of the group to include P. atelopoides and P. tomopterna.